Evaluation of Revised National Tuberculosis Control Program among Ten Designated Microscopy Centers of West Tripura: A Cross-Sectional Study - Goyal, Ankita; Kumar, Aman; Vashishth, Tuhin; Kumari, Priyanka; Pachauri, Rajat K. (Annals of the National Academy of Medical Sciences (India), 2022)
Objectives Pulmonary tuberculosis (TB) is chronic communicable bacterial disease caused by Mycobacterium tuberculosis. The objective was to assess the performance in terms of knowledge and practice of pulmonary tuberculosis (PTB) program among directly observed treatment short course (DOTS) provider, lab technician, senior treatment supervisor (STS), senior tuberculosis laboratory supervisor (STLS), factors affecting knowledge and practice of PTB program, rate of detection, cure rate and to identify the gaps and underlying contributing factors in terms of supply, manpower, and infrastructure.Materials and Methods A cross-sectional study was conducted on knowledge and practice of PTB program among DOTS Provider, lab technician, STS, STLS in ten designated tuberculosis center of West Tripura from May 2018 to April 2019. Simple random sampling method was followed for selecting DOTS provider and sample size of 50 was taken.Results Majority (40.0%) of patients were in the age group of 31 to 40 years and mean age of 40.98 ± 10.13 years. Females and males were 68.0 and 32.0%, respectively. Among DOTS provider, 66.0% had served for more than 5 years of service and 84.0% of them had verified address before starting the treatment.Conclusion Majority of the DOTS provider had satisfactory knowledge and practice about PTB program. Proportion of the medical officers attending DOTS training was inadequate and there were adequate number of the health care workers who had attended DOTS training. There were no gaps found in proportion of the cases receiving the supervised treatment.
Keywords: pulmonary tuberculosis; program; knowledge; association; treatment